2021
DOI: 10.3390/nu13020707
|View full text |Cite
|
Sign up to set email alerts
|

Accidental Consumption of Aspartame in Phenylketonuria: Patient Experiences

Abstract: Aspartame is a phenylalanine containing sweetener, added to foods and drinks, which is avoided in phenylketonuria (PKU). However, the amount of phenylalanine provided by aspartame is unidentifiable from food and drinks labels. We performed a cross-sectional online survey aiming to examine the accidental aspartame consumption in PKU. 206 questionnaires (58% female) were completed. 55% of respondents (n = 114) were adults with PKU or their parent/carers and 45% (n = 92) were parents/carers of children with PKU. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…Importantly, aspartame content is exempted from inclusion in the labelling of alcoholic drinks. [ 11 ]. Several examples were given of inconsistent aspartame identification on the labels of fruit squashes or drinks bought from shop vendors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, aspartame content is exempted from inclusion in the labelling of alcoholic drinks. [ 11 ]. Several examples were given of inconsistent aspartame identification on the labels of fruit squashes or drinks bought from shop vendors.…”
Section: Discussionmentioning
confidence: 99%
“…Several examples were given of inconsistent aspartame identification on the labels of fruit squashes or drinks bought from shop vendors. Detailed information about the perceptions of aspartame and food labelling of patients or caregivers of patients with PKU has been reported [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent consumer pressure from the food industry and busy working adult lives has led to increased dependence on processed foods which are commonly not low in Phe or may have unreliable protein labelling information [ 25 ]. In addition, societal efforts to reduce the sugar content of foods has also led to sugar replacement by artificial sweeteners such as aspartame, another unquantified source of Phe [ 26 ]. Pre-existing social disadvantages such as parental poor literacy, health literacy and poverty may render some children particularly vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…A UK study found many people suffering from phenylketonuria choose products without being aware of the amount of aspartame they contain; it is believed that the sugar tax in the country increases the use of sugar substitutes, including aspartame. In addition, approximately 25% of patients reported consuming aspartame with medications [134]. Studies have found aspartame and phenylalanine levels to vary between soft drinks; however, some consist of small amounts of APM and Phe, and could be safely consumed by patients with hyperphenylalaninemia and those treated with 2-(2-nitro-4trifluoromethylbenzoyl)-1,3-cyclohexanedione (NTBC) (van Vliet et al, 2020).…”
Section: Phenyloketonuriamentioning
confidence: 99%